Anthropometric characteristics of top water polo players in relation to playing position in the game - Niksic, E.; Beganovic, E.; Mirvic, E. (Journal of Physical Education and Sport, 2020)
Modern water polo is characterized by fast and attractive play as well as mutual contacts of players, which requires specific anthropometric characteristics from water polo players. Morphology is important in every sport, which is why top water polo players are selected and shaped based on the requirements of the water polo game. The anthropometric characteristics that characterize today's top water polo players include a higher height and longer limbs with a narrower waist and wider shoulders. Body weight has increased. The level of muscle mass increases in relation to adipose tissue. In any sport, success is determined by analysis of various interrelated anthropological dimensions. The aim of this study was to determine differences in the anthropometric characteristics of top water polo players in relation to their playing positions. The study was conducted on a sample of 208 water polo players, who were participants of the 34th LEN European Water Polo Championships. Statistically significant differences in body height were recorded between the positions of wing and center back, center forward, and goal keeper (p <0.05). Differences in body weight were recorded between the positions of wing and center back, center forward (p <0.05), center forward and center back, and goal keeper (p <0.05), and differences in BMI were recorded between the positions of center back and wing, center forward, and goal keeper (p <0.05). Morphological characteristics play a vital role in determining the success of athletes as confirmed by the results of our study in which there were statistically significant differences in the morphological characteristics. The highest body height and BMI were recorded in central defenders, while attackers had the highest body weight.